Field Guide to Identify the Common Casuarina (Australian Pine) Species in Florida - William S. Castle; Michael Andreu (EDIS)
This 6-page fact sheet that was submitted for sunset review provides practical information and photographs to anyone interested in field identification of Australian Pine. Written by William S. Castle and Michael Andreu, and originally published by the UF Department of Horticultural Sciences, May 2008. Reviewed July 2017.